Arrhythmic effects of Epac‐mediated ryanodine receptor activation in Langendorff‐perfused murine hearts are associated with reduced conduction velocity. (June 2017) - Li, Mengye; Hothi, Sandeep S; Salvage, Samantha C; Jeevaratnam, Kamalan; Grace, Andrew A; Huang, Christopher L‐H
Summary: Recent papers have attributed arrhythmic substrate in murine RyR2‐P2328S hearts to reduced action potential (AP) conduction velocities (CV), reflecting acute functional inhibition and/or reduced expression of sodium channels. We explored for acute effects of direct exchange protein directly activated by cAMP (Epac)‐mediated ryanodine receptor‐2 (RyR2) activation on arrhythmic substrate and CV. Monophasic action potential (MAP) recordings demonstrated that initial steady (8 Hz) extrinsic pacing elicited ventricular tachycardia (VT) in 0 of 18 Langendorff‐perfused wild‐type mouse ventricles before pharmacological intervention. The Epac activator 8‐CPT (8‐(4‐chlorophenylthio)‐2′‐ O ‐methyladenosine‐3′, 5′‐cyclic monophosphate) (VT in 1 of 7 hearts), and the RyR2 blocker dantrolene, either alone (0 of 11) or with 8‐CPT (0 of 9) did not then increase VT incidence ( P >.05). Both progressively increased pacing rates and programmed extrasystolic (S2) stimuli similarly produced no VT in untreated hearts (n=20 and n=9 respectively). 8‐CPT challenge then increased VT incidences (5 of 7 and 4 of 8 hearts respectively; P <.05). However, dantrolene, whether alone (0 of 10 and 1 of 13) or combined with 8‐CPT (0 of 10 and 0 of 13) did not increase VT incidence relative to those observed in untreated hearts ( P >.05). 8‐CPT but not dantrolene, whether alone or combined with 8‐CPT, correspondingly increased AP latencies (1.14±0.04 (n=7), 1.04±0.03 (n=10), 1.09±0.05 (n=8) relative to respective control values). In contrast, AP durations, conditions for 2:1 conduction block and ventricular effective refractory periods remained unchanged throughout. We thus demonstrate for the first time that acute RyR2 activation reversibly induces VT in specific association with reduced CV.